1971
DOI: 10.1152/jn.1971.34.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of stimulus intensity on response of auditory nerve fibers in the squirrel monkey.

Abstract: run as well as after every eight consecutive stimulus presentations. RESULTS Relation between shape of response area and best frequency of fiber

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
2
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(123 citation statements)
references
References 7 publications
9
111
2
1
Order By: Relevance
“…These findings appear to be consistent with some of the descriptions of auditory nerve activity accompanying changes of intensity that were generally independent of the frequency of the tones (Rose et al, 1971;Heil and Neubauer, 2001). High spontaneous rate nerve fibers generally have lower thresholds and exhibit firing rate saturation at low stimulus intensities.…”
Section: Changes Of Intensitysupporting
confidence: 87%
See 2 more Smart Citations
“…These findings appear to be consistent with some of the descriptions of auditory nerve activity accompanying changes of intensity that were generally independent of the frequency of the tones (Rose et al, 1971;Heil and Neubauer, 2001). High spontaneous rate nerve fibers generally have lower thresholds and exhibit firing rate saturation at low stimulus intensities.…”
Section: Changes Of Intensitysupporting
confidence: 87%
“…Fig. 9a summarizes the amplitude and latency of N100 to changes of intensity (left) while the right side schematically represents auditory nerve single unit response properties (based on Rose et al, 1971) for both 250 and 4000 Hz accompanying changes of intensity. Note that both the numbers of units and their rate or synchrony of discharge increase relatively equivalently for low and high frequency tones, consistent with the finding that N100 amplitudes for intensity changes of low and high frequencies were not significantly different.…”
Section: Changes Of Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…3). Such plots have been previously named 'response areas' in the context of responses of cochlear afferent fibers to tones (e.g., Rose et al, 1971;Geisler et al, 1974). Indeed, the family of basilar-membrane iso-SPL curves depicted in Fig.…”
Section: Responses To Tone Pipsmentioning
confidence: 99%
“…Hind et al [16] and Rose et al [37,38] found that, for a large range of stimulus intensities, histograms of the responses of auditory nerve fibers to continuous pure tones have shapes that closely resemble half-wave rectified sine waves and that histograms of the responses to two-tone complexes also have shapes that are similar to the waveforms of a half-wave rectified combination of the same two frequencies.…”
Section: Introductionmentioning
confidence: 99%